Analisis Islamic Social Reporting pada Perbankan Syariah di Indonesia - Rizki Setiawan; Hasbi Assidiki Mauluddi; Dadang Hermawan (Journal of Applied Islamic Economics and Finance, 2021)
This study aims to determine and analyze the effect of profitability, liquidity, company size and leverage on Islamic Social Reporting on Islamic commercial banks in Indonesia in the 2014-2018 period with the board of commissioners as a moderating variable. The main problem in this study is how much influence the profitability of the ISR is calculated through return on assets (ROA), namely the ratio between net income and total assets, liquidity to ISR calculated through the current ratio (CR), namely the ratio between current assets with current debt, the size of the company against ISR calculated by the natural logarithm of total assets, the effect of leverage on ISR calculated through the debt to assets rasio (DAR) and the board of commissioners as a moderating variable measured by the number of sharia board of commercial banks. The sampling technique using purposive sampling and obtained 7 company samples from a total of 14 population of Muamalat Indonesia Bank, BRI Syariah, BNI Syariah Bank, Mandiri Syariah Bank, Mega Syariah Bank, Syariah Bank Bukopin, BCA Syariah Bank. This type of research used in this study is quantitative. The data used in this study are secondary data in the form of finansial and annual reports. Data analysis techniques that researchers use are descriptive statistical analysis, classic assumption tests, Modereted Regression Analysis (MRA), partial hypothesis testing (t test), simultaneous hypothesis testing (f test), and coefficient of determination (R test). The R test of this study shows that the overall contribution of the independent variables, namely Profitability, Liquidity, Firm Size and Leverage to the dependent variable, namely ISR which is moderated by the Board of Commissioners variable is 70%, while 30% is determined by other variables not examined in this study. The F test of this study shows that simultaneously profitability, liquidity, firm size and leverage have a positive effect on ISR. The T test shows that profitability, liquidity, company size and leverage partially affect the ISR. The results of the moderation test are only liquidity and company size which are well moderated by the size of the board of commissioners in conducting ISR disclosures.